Wyruszając w nieznane: ale czy na pewno? Między teorią a praktyką „pisarstwa naukowego” pracy dyplomowej (na przykładzie psychologii) - Małysz, Zbigniew (Kultura-Społeczeństwo-Edukacja, 2025)
The article focuses on the relationship between the (scientific) theory and practice of preparing a diploma thesis in academic education (specifically, in the field of social sciences, as illustrated by psychology). The study presented here is of a methodological and synthesizing nature/aims, and was prepared: (a) to fill the re-search gap observed in this area (especially in the absence of studies indicating the location of a (good) scien-tific theory on the Internet), (b) using the analytical-synthetic method and the existing data analysis method.The author discuss here a wide spectrum of aspects pertaining to such analytical problems as: (1) the essence and functional significance of a scientific theory (in science), (2) the location of a (good) scientific theory in the subject matter literature, (3) how to apply a scientific theory (while preparing a diploma the-sis), (4) the location of a scientific theory in online scientific search engines, (5) the methodology problems essential for the process of preparing a diploma thesis.